Depth of invasion on pathological outcomes in clinical low‐stage oral tongue cancer patients. (29th May 2018) - Masood, Maheer M.; Farquhar, Douglas R.; Vanleer, Jessica P.; Patel, Samip N.; Hackman, Trevor G.
Abstract: Objectives: Depth of invasion was added to the eighth edition American Joint Committee on Cancer guidelines for T staging of HPV‐negative oral cavity squamous cell carcinoma. Our aim was to determine the impact of depth of invasion on pathological variables and outcomes in low‐stage tongue cancer patients. We also examine the impact of tumor thickness and tumor clinical staging for comparison. Subjects and Methods: All clinical T1/T2 N0 HPV‐negative tongue squamous cell carcinoma patients who received elective neck dissections at our institution between 2000 and 2015 were included. Logistic regression models and Cox proportional hazard models were used to examine pathological variables, recurrence, and 3‐year disease‐free survival. Results: Sixty‐seven patients met criteria; the mean age was 52.0 ( SD : 17.7). Depth of invasion was a significant predictor of occult metastasis (OR: 2.0, p  = 0.05) and lymphovascular invasion (OR: 4.1, p  = 0.02), and tumor thickness was a significant predictor of lymphovascular invasion (OR: 3.3, p  = 0.04). None of the variables were predictive of recurrence or disease‐free survival. Conclusion: Depth of invasion at biopsy may be a potential useful metric to inform on regional management selection in this radiographic node‐negative population.